Glioblastoma endothelium drives bevacizumab‐induced infiltrative growth via modulation of PLXDC1. Issue 6 (16th December 2018) - Falchetti, Maria Laura; D'Alessandris, Quintino Giorgio; Pacioni, Simone; Buccarelli, Mariachiara; Morgante, Liliana; Giannetti, Stefano; Lulli, Valentina; Martini, Maurizio; Larocca, Luigi Maria; Vakana, Eliza; Stancato, Louis; Ricci‐Vitiani, Lucia; et al.
Abstract : Bevacizumab, a VEGF‐targeting monoclonal antibody, may trigger an infiltrative growth pattern in glioblastoma. We investigated this pattern using both a human specimen and rat models. In the human specimen, a substantial fraction of infiltrating tumor cells were located along perivascular spaces in close relationship with endothelial cells. Brain xenografts of U87MG cells treated with bevacizumab were smaller than controls ( p = 0.0055; Student t ‐test), however, bands of tumor cells spread through the brain farther than controls ( p < 0.001; Student t ‐test). Infiltrating tumor Cells exhibited tropism for vascular structures and propensity to form tubules and niches with endothelial cells. Molecularly, bevacizumab triggered an epithelial to mesenchymal transition with over‐expression of the receptor Plexin Domain Containing 1 (PLXDC1). These results were validated using brain xenografts of patient‐derived glioma stem‐like cells. Enforced expression of PLXDC1 in U87MG cells promoted brain infiltration along perivascular spaces. Importantly, PLXDC1 inhibition prevented perivascular infiltration and significantly increased the survival of bevacizumab‐treated rats. Our study indicates that bevacizumab‐induced brain infiltration is driven by vascular endothelium and depends on PLXDC1 activation of tumor cells. Abstract : What's new? Bevacizumab, a VEGF‐targeting monoclonal antibody, has been observed to trigger an infiltrative growth pattern in glioblastoma as an escape mechanism. The mechanisms underlying this gliomatosis‐like growth pattern, however, remain unclear. Here, the authors found that the infiltrative growth pattern occurs mostly along perivascular spaces and relies on the over‐expression of PLXDC1 by tumor cells and on the restoration of the endothelial component of blood brain barrier. Altogether, the data show that the brain infiltration induced by bevacizumab is mainly driven by the vascular endothelium. Importantly, inhibition of PLXDC1 prevents bevacizumab‐induced infiltrative growth, resulting in significant increase of survival.